2020
DOI: 10.1371/journal.pone.0232322
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ awareness, attitude and associated factors towards self-medication in Hail, Saudi Arabia

Abstract: Objectives To determine the factors motivating the consumers towards self-medication, the intended indications and the consumers' perceptions about complications that may arise due to its use. Design Cross-sectional community based prospective study Place and duration of study Community pharmacies located at various locations of Hail, Saudi Arabia from January 2019 to March 2019. Methods The subjects of this cross-sectional study were people visiting community pharmacies for self-medication. Data on 663 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
18
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 29 publications
10
18
3
5
Order By: Relevance
“…Self-medication practice was more prominent in ages younger than 40 years old, and a strong correlation was found between age and SM. This contradicts with a study conducted in Egypt in which selfmedication was prevalent in ages older than 40 years old [3], while it correlates with other studies held in Saudi Arabia [17], Lebanon [6], and Brazil [9] which also revealed a predominance in younger ages.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Self-medication practice was more prominent in ages younger than 40 years old, and a strong correlation was found between age and SM. This contradicts with a study conducted in Egypt in which selfmedication was prevalent in ages older than 40 years old [3], while it correlates with other studies held in Saudi Arabia [17], Lebanon [6], and Brazil [9] which also revealed a predominance in younger ages.…”
Section: Discussioncontrasting
confidence: 99%
“…Headache, cough/ u, and body aches were the main conditions to treat. These ndings came in concordance with these of a study in Saudi Arabia [17] in which headache, u and cough were the predominant indications. However, fever was also a predominant indication in Saudi Arabia, while suffering from body aches was more common in our study.…”
Section: Discussionsupporting
confidence: 91%
“…14 educated responded affirmatively for receiving self-medication. 26 Similar trend was reported by a study conducted in Nepal. 27 According to our findings, two-thirds (63.6 percent) of the participants used non-prescribed medication for 1-3 days, which is consistent with previous findings reported in Al Madina city.…”
Section: Discussionsupporting
confidence: 85%
“…These findings are consistent with previous studies conducted in Jordan, 56 Nigeria, 56 India, 47 Ethiopia, 6,46 Egypt, 57 and Saudi Arabia. 58 In contrast, it isn’t in line with previous studies in India and Ethiopia, that they practice SM for Diabetes mellitus, Malaria, and Epilepsy. 59,60 The predominant reasons to practice self-medication were similarity of symptoms with past illness (33.49%), followed by illness as mild (19.17%), and self-medication is cheaper (18.24%).…”
Section: Discussionmentioning
confidence: 93%